Extracellular Sunflower Proteins: Evidence on Non-classical Secretion of a Jacalin-Related Lectin - Pinedo, Marcela Lilian (2012)
Extracellular proteins from sunflower seedlings were analyzed by electrophoresis followed by peptide mass fingerprinting. Tentative identification revealed novel proteins for this crop. A significant number of those proteins were not expected to be extracellular because they lacked the typical signal peptide responsible for secretion. In silico analysis showed that some members of this group presented the characteristic disordered structures of certain non-classical and leaderless mammalian secretory proteins. Among these proteins, a putative jacalin-related lectin (Helja) with a mannose binding domain was further isolated from extracellular fluids by mannose-affinity chromatography, thus validating its identification. Besides, immunolocalization assays confirmed its extracellular location. These results showed that a lectin, not predicted to be secreted in strict requirement of the N-terminal signal peptide, occurs in a sunflower extracellular compartment. The implications of this finding are discussed.